Acute and chronic changes in rat soleus muscle after high‐fat high‐sucrose diet. Issue 10 (22nd May 2017) - Collins, Kelsey H.; Hart, David A.; Smith, Ian C.; Issler, Anthony M.; Reimer, Raylene A.; Seerattan, Ruth A.; Rios, Jaqueline L.; Herzog, Walter
Abstract: The effects of obesity on different musculoskeletal tissues are not well understood. The glycolytic quadriceps muscles are compromised with obesity, but due to its high oxidative capacity, the soleus muscle may be protected against obesity‐induced muscle damage. To determine the time–course relationship between a high‐fat/high‐sucrose (HFS) metabolic challenge and soleus muscle integrity, defined as intramuscular fat invasion, fibrosis and molecular alterations over six time points. Male Sprague‐Dawley rats were fed a HFS diet ( n  = 64) and killed at serial short‐term (3 days, 1 week, 2 weeks, 4 weeks) and long‐term (12 weeks, 28 weeks) time points. Chow‐fed controls ( n  = 21) were killed at 4, 12, and 28 weeks. At sacrifice, animals were weighed, body composition was calculated (DXA), and soleus muscles were harvested and flash‐frozen. Cytokine and adipokine mRNA levels for soleus muscles were assessed, using RT‐qPCR. Histological assessment of muscle fibrosis and intramuscular fat was conducted, CD68 + cell number was determined using immunohistochemistry, and fiber typing was assessed using myosin heavy chain protein analysis. HFS animals demonstrated significant increases in body fat by 1 week, and this increase in body fat was sustained through 28 weeks on the HFS diet. Short‐term time‐point soleus muscles demonstrated up‐regulated mRNA levels for inflammation, atrophy, and oxidative stress molecules. However, intramuscular fat, fibrosis, and CD68 + cell number were similar to their respective control group at all time points evaluated. Therefore, the oxidative capacity of the soleus may be protective against diet‐induced alterations to muscle integrity. Increasing oxidative capacity of muscles using aerobic exercise may be a beneficial strategy for mitigating obesity‐induced muscle damage, and its consequences. Abstract : The purpose of this paper was to determine the time–course relationship between a high‐fat high‐sucrose (HFS) metabolic challenge and soleus muscle integrity, defined as intramuscular lipid content fibrosis and molecular alterations over six time points. We found that intramuscular fat, fibrosis, and CD68 + cell number were similar in HFS soleus muscles to their respective control group at all time points evaluated. Therefore, the high oxidative capacity of the soleus may be protective against diet‐induced alterations to muscle integrity.